Friendly Home and Inhabitants' Morality: Mutual Relationships - Nartova-Bochaver, Sofya K.; Kuznetsova, Valeriya B. (Frontiers in Psychology, 2018)
The study is aimed at investigating the connection between the friendliness of the home environment and the moral motives’ level. The friendliness of the home environment includes two aspects: the number of functions provided by home (functionality) and the congruence of these functions with inhabitants’ needs (relevance). The theoretical framework of the study was formed by research and ideas emphasizing the interplay between people and their environments. We hypothesized that the friendliness of the home environment and inhabitants’ moral motives would have a reciprocal relationship: the friendlier the home the higher the inhabitants’ moral motives’ level, and, vice versa, the higher the person’s moral motives’ level the more positive home image. The respondents were 550 students (25% male). The Home Environment Functionality Questionnaire, the Home Environment Relevance Questionnaire, and the Moral Motivation Model Scale were used. As expected, it was found that the friendliness of the home environment and the inhabitants’ moral motives are in reciprocal synergetic relationships. Relevance formed more nuanced correlation patterns with moral motives than functionality did. Functionality predicted moral motives poorly whereas moral motives predicted functionality strongly. Finally, relevance and moral motives were found to be in mutual relationships whereas the perceived functionality was predicted by moral motives only.